Turismo rural como alternativa de desarrollo local para la parroquia San Pedro de Vilcabamba - Arévalo Abad, Carlos Alberto (2023)
The San Pedro de Vilcabamba parish, belonging to the canton of Loja, is a town possessing cultural richness, with great natural resources, surrounded by a crystalline river, surrounded by hills and mountains, with an incomparable flora and fauna, this parish is the cradle of own enterprises of its working people. Despite having many necessary factors to generate tourist activities, the parish has been stagnant in tourism issues or activities, under this problem arises the need to raise the research work called "Rural tourism as an alternative for local development for the parish of San Pedro de Vilcabamba”. The research work contemplates in its first objective the tourist diagnosis of the parish, resulting in having a clear picture of the current situation of the town, with respect to having necessary and basic services to be able to develop tourist activity in the community. As a second objective, the profile of the potential visitor to the town is analyzed, which allows establishing necessary strategies focused on the future tourist and thus being able to develop tourist products necessary to energize the parish. Finally, in the last objective, the necessary and fundamental strategies are proposed to develop tourism from a rural perspective, as well as the creation of a tourist route that includes the main enterprises and attractions of the parish in the first instance, in the same way creating the brand tourism of the parish to position itself within the tourism market.